Literasi Keuangan Dan Gaya Hidup Ibu Rumah Tangga Dalam Membentuk Perilaku Keuangan Di Tasikmalaya - Deasy Lestary Kusnandar; Dian Kurniawan (Sains: Jurnal Manajemen dan Bisnis, 2020)
This study aims to determine the effect of financial literacy on financial behavior with lifestyle as a mediation variable. The location of this research is in Tasikmalaya. This research is a kind of quantitative research using survey method given to Housewife in Tasikmalaya city. The object of research in this study is the financial literacy, lifestyle, and financial behavior. Determination of the number of samples in this study are as many as 100 respondents with the sampling method used is to use judgment sampling. The analysis used is Structural Equation Modeling (SEM) analysis. This analysis is assisted by using the AMOS 21. The results of this study indicate that financial literacy does not affect in financial behaviour. While life style can mediate influence financial literacy on financial behaviour;s housewife in Tasikmalaya.